Use of minimally invasive tissue sampling to determine the contribution of diarrheal diseases to under-five mortality and associated co-morbidities and co-infections in children with fatal diarrheal diseases in Africa and Bangladesh. - Portia Chipo Mutevedzi; Zachary J Madewell; Karen L Kotloff; Quique Bassat; Percina Joao Chirinda; Anelsio C A Cossa; Elisio G Xerinda; Victor Akelo; Paul K Mitei; Elizabeth Oele; Richard Omore; Dickens Onyango; et al. (PLOS Global Public Health, 2025)
Achieving the Sustainable Development Goal of reducing child mortality to <25 deaths per 1000 live births by 2030 requires strategies to prevent diarrheal disease-related morbidity and mortality. Accurate etiological diagnosis is essential. This study used postmortem diagnostics to investigate the contribution of diarrhea to under-5 mortality and examine co-morbidities and co-infections in Africa and South Asia. Child Health and Mortality Prevention Surveillance (CHAMPS) generates data on child deaths through minimally invasive tissue sampling, clinical record review, and verbal autopsies. Multidisciplinary panels assign cause(s) of death using WHO International Classification of Diseases. This analysis included deaths among children aged 1-59 months enrolled from 18 December 2016-31 December 2023 across six African sites (Ethiopia, Mali, Kenya, Sierra Leone, Mozambique, South Africa) and Bangladesh. Of 1517 deaths assessed, diarrhea was in the causal pathway in 240 (15.8%). The proportion of diarrhea-related deaths was highest in Ethiopia (41.0%, 34/83), followed by Bangladesh, (30.0%, 3/10), Mozambique (21.7%, 56/258), Mali (17.5%, 18/103), Kenya (13.9%, 51/366), Sierra Leone (12.8%, 46/358), and South Africa (9.4%, 32/339). Diarrhea was underlying cause in 44.2% (106/240) of cases and immediate/antecedent cause in 58.3% (140/240), with some deaths involving multiple roles in the causal chain. When diarrhea was underlying cause, sepsis (33.0%) and lower respiratory infections (25.5%) were common downstream conditions; when an antecedent/immediate cause, leading underlying causes were malnutrition (64.3%) and HIV (13.6%). No pathogen was identified in 49.6% (119/240) of diarrhea-related deaths; among these, diarrhea was underlying cause in 42.9%. Among the 121 pathogen-attributed deaths, the most frequent were EAEC (34.7%), typical EPEC (15.7%), Shigella/EIEC (14.0%), ST-ETEC (12.4%), rotavirus (26.4%), and adenovirus (non-40/41: 19.0%; 40/41: 5.0%). These pathogens were frequently identified as co-infections. Diarrheal disease accounted for a substantial share of child deaths across CHAMPS sites. Reducing mortality will require preventing diarrhea and addressing key contributors such as malnutrition and HIV.